Garbage Monitoring System with IoT - Bhattacharya, Riju; Manik, Geetanjali; Verma , Khushbu (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
In today's world, time is a vital issue which cannot be managed by noticing every phenomenon with our tight schedule. So Automatic systems are being preferred over the manual system to make life simpler and more comfortable in all aspects; certain actions are taken to improve the level of cleanliness in the country. People are getting more active in doing all the things possible to clean their surroundings. We are trying to build a system which will notify the user to empty the bin on time. In this system, we will put a sensor on top of the garbage bin which will detect the total level of garbage inside it according to the total size of the bin. By using this system, people do not have to check all the systems manually. What our system does is it gives a real- time indicator of the garbage level in a trashcan at any given time.